Clinical exercise testing: basic principles and practice. Issue 3 (September 2017) - Laveneziana, Pierantonio; Ward, Susan; Neder, J. Alberto; Poberezhets, Vitalii
The ERS course on "Clinical exercise testing: basic principles and practice" was held in Rome, Italy, from February 23 to 24, 2017. This is the first time that the course has taken place as a 2-day basic course. Previously, a 3-day course had taken place six times. Overall, 94% of participants were satisfied and declared that they would change their daily practice after attending the course; some of them even felt confident to start practicing clinical exercise testing. This was a great success. Faculty and delegates of an @ERStalk course on clinical exercise testing describe their experiences http://ow.ly/dPwB30dxr8v